Regulating the Crypto Ecosystem : The Case of Stablecoins and Arrangements - Bains, Parma (FinTech Notes; FinTech Notes, 2022)
Stablecoins have experienced periods of rapid growth, accelerated links with traditional finance. Without proper regulation, contagion risks to wider financial sector will increase. Global regulation for stablecoins should be comprehensive, consistent, risk-based, flexible, and focus on their structural features and use. Requirements on stablecoins should cover the entire ecosystem and all its key functions, and there should be additional oversight for systemic stablecoin arrangements. In markets where risks are growing quickly, authorities should take immediate action by using all the tools at their disposal. This note provides key elements that should feature in any regulatory arrangement. For effective implementation, domestic and international collaboration are key.